2022
DOI: 10.1111/aogs.14322
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of apical vaginal prolapse with minimal mesh repair (Uphold): patient‐reported long‐term outcomes and mesh‐related complications

Abstract: Introduction To evaluate patient‐reported outcomes and clinical findings after surgery for apical prolapse with the transvaginal Uphold mesh technique. Moreover, to evaluate the rate of mesh‐related complications. Material and Methods A historical cohort study of patients who underwent surgery from January 1, 2012 to April 30, 2019, at Aarhus University Hospital, Denmark. Pelvic examination and patient completion of questionnaires were performed in 2018–2019. Information on adverse events and reoperations was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…This is different from a study done in Denmark, which reported wound infection in 0.5% of patients after surgery. 22 Likewise, a case series study carried out in the UK reported a lower wound infection rate of 2%. 23 This is an alarming situation that requires further investigation.…”
Section: Discussionmentioning
confidence: 97%
“…This is different from a study done in Denmark, which reported wound infection in 0.5% of patients after surgery. 22 Likewise, a case series study carried out in the UK reported a lower wound infection rate of 2%. 23 This is an alarming situation that requires further investigation.…”
Section: Discussionmentioning
confidence: 97%
“…However, it should be noted that those complications are serious and worth consideration, especially the ureteric mesh erosion ( 22 ). In a different series reporting on the mesh-related complications after the uphold procedure, the erosion and pelvic pain rates were 4% and 5% respectively ( 26 ). Another long-term follow up study demonstrated that the 24-month urinary retention rate related to mesh inlay was 2.5% and vaginal adhesions occurred in 1.2% ( 27 ).…”
Section: Discussionmentioning
confidence: 99%